Spontaneous Superficial Femoral Artery Mycotic Aneurysm. (26th February 2021) - Vijaykumar, Kalpana; Tay, Jia Sheng; Tang, Tjun Yip; Choke, Edward Tieng Chek
Abstract : Peripheral artery mycotic aneurysms are rare occurrences. In this case, we review a 52-year-old lady with poorly controlled diabetes who developed a spontaneous left superficial artery mycotic aneurysm. She underwent excision and subsequent extra-anatomic bypass with a great saphenous vein graft. She had full functional recovery after a short period of rehabilitation.